Dynamics of Application of Halal Certification on Medicine Products in Indonesia - Asmuni Asmuni; M. Jamil; Fitri Rafianti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Products are "goods and / or services related to food, beverages, drugs, cosmetics, chemical products, biological products, genetically engineered products, as well as used goods that are used, used or utilized by the public", while the halal certificate is a certificate issued by the Central or Provincial MUI regarding the case of a food product, foodstuff, beverage and medicine and cosmetics produced by the company after being examined and declared halal by an institution authorized to issue a halal product certification. In Article 4 of Law No. 33 of 2014 concerning the guarantee of halal products it states that "Products that enter, circulate and are traded in the territory of Indonesia must be certified halal". Normatively, the article clearly stipulates that drugs that enter, circulate and are traded in the territory of Indonesia must be guaranteed halal. However, the halal certification process for medicines in Indonesia is waiting for a long time due to various dynamics, this is the content of researchers seeing the gap between Law Number 33 of 2014 and the current reality, we should be able to reflect on other countries as well. Which